Oxygen-sensing scaffolds for 3-dimensional cell and tissue culture. (1st April 2015) - Jenkins, James; Dmitriev, Ruslan I.; Morten, Karl; McDermott, Kieran W.; Papkovsky, Dmitri B.
Graphical abstract: Microporous polystyrene-based scaffolds stained with phosphorescent O2 -sensitive dye inform on O2 gradients within 3D cultures. Abstract: Porous membrane scaffolds are widely used materials for three-dimensional cell cultures and tissue models. Additional functional modification of such scaffolds can significantly extend their use and operational performance. Here we describe hybrid microporous polystyrene-based scaffolds impregnated with a phosphorescent O2 -sensitive dye PtTFPP, optimized for live cell fluorescence microscopy and imaging of O2 distribution in cultured cells. Modified scaffolds possess high brightness, convenient spectral characteristics (534 nm excitation, 650 nm emission), stable and robust response to pO2 in phosphorescence intensity and lifetime imaging modes (>twofold response over 21/0% O2 ), such as confocal PLIM. They are suitable for prolonged use under standard culturing conditions without affecting cell viability, and for multi-parametric imaging analysis of cultured cells and tissue samples. We tested the O2 scaffolds with cultured cancer cells (HCT116), multicellular aggregates (PC12) and rat brain slices and showed that they can inform on tissue oxygenation at different depths and cell densities, changes in respiration activity, viability and responses to drug treatment. Using this method multiplexed with staining of dead cells (CellTox Green) and active mitochondria (TMRM), we demonstrated that decreased O2 (20–24 μM) in scaffold corresponds to highest expression of tyrosine hydroxylase in PC12 cells. Such hypoxia is also beneficial for action of hypoxia-specific anti-cancer drug tirapazamine (TPZ). Thus, O2 scaffolds allow for better control of conditions in 3D tissue cultures, and are useful for a broad range of biomaterials and physiological studies.